An updated model to enhance knowledge sharing among stakeholders in jordanian hospitals using social networks - Alhalhouli Z.T.; Hassan Z.B.H.J.; Abualkishik A.M. (2023)
Survival of any organization heavily depends on knowledge sharing, however, the variables that enhance or dissuade knowledge sharing behaviors in the Jordanian hospitals has not been poorly recognized. Therefore, this paper is aimed at determining the obstacles that prevent stakeholders in Jordanian hospitals from sharing their knowledge; and furthermore we have developed a conceptual model, based on Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM), to improve our understanding in terms of the factors, which affect knowledge sharing behaviors of knowledge workers in the Jordanian hospitals. To achieve the objective of examining the barriers that hinder the stakeholders from knowledge sharing in Jordanian hospitals, we have conducted an interview survey with the stakeholders in the Jordanian hospitals, to get their viewpoints. Therefore, we interviewed 15 of the workers in the various sectors in Jordanian hospitals and we have analyzed the results, which showed that, 18 out of 36 universal barriers are affecting the knowledge sharing behavior. By comparing these results with previous studies, we developed a conceptual model, to improve and encourage stakeholders to share knowledge, among them. IDOSI Publications, 2013.